Alternative Copper-Based Single-Atom Nanozyme with Superior Multienzyme Activities and NIR-II Responsiveness to Fight against Deep Tissue Infections - Bai Jiaxiang; Feng Yonghai; Li Wenming; Cheng Zerui; Rosenholm Jessica M; Yang Huilin; Pan Guoqing; Zhang Hongbo; Geng Dechun (American Association for the Advancement of Science, 2025)
Nanozymes are considered to represent a new era of antibacterial agents, while their antibacterial efficiency is limited by the increasing tissue depth of infection. To address this issue, here, we report a copper and silk fibroin (Cu-SF) complex strategy to synthesize alternative copper single-atom nanozymes (SAzymes) with atomically dispersed copper sites anchored on ultrathin 2D porous N-doped carbon nanosheets (CuN x -CNS) and tunable N coordination numbers in the CuN x sites (x = 2 or 4). The CuN x -CNS SAzymes inherently possess triple peroxidase (POD)-, catalase (CAT)-, and oxidase (OXD)-like activities, facilitating the conversion of H2O2 and O2 into reactive oxygen species (ROS) through parallel POD- and OXD-like or cascaded CAT- and OXD-like reactions. Compared to CuN2-CNS, tailoring the N coordination number from 2 to 4 endows the SAzyme (CuN4-CNS) with higher multienzyme activities due to its superior electron structure and lower energy barrier. Meanwhile, CuN x -CNS display strong absorption in the second near-infrared (NIR-II) biowindow with deeper tissue penetration, offering NIR-II-responsive enhanced ROS generation and photothermal treatment in deep tissues. The in vitro and in vivo results demonstrate that the optimal CuN4-CNS can effectively inhibit multidrug-resistant bacteria and eliminate stubborn biofilms, thus exhibiting high therapeutic efficacy in both superficial skin wound and deep implant-related biofilm infections.